5-A-SIDE SOCCER: PREVALENCE OF SPORTS INJURIES IN BRAZILIAN TEAM PLAYERS - Santos,Thálita Gonçalves (2021)
ABSTRACT Introduction: 5-a-side soccer is a sports modality exclusively for athletes with vision impairment (VI) classified as blind - B1 (Blind 1) by the visual classification process. Type of impairment and high-performance training are factors that contribute to the development of sports injuries. Objective: The purpose of this study was to characterize the prevalence of sports-related injuries in visually disabled athletes of the Brazilian 5-a-side soccer team. Methods: The method was defined as a descriptive, longitudinal, epidemiological study. The sample was composed of ten male athletes, members of the Brazilian 5-a-side soccer team, including two athletes without VI and eight athletes with the B1 visual classification, who participated in competitions in 2014. The questionnaire for the data collection was based on the Sport Injuries Protocol for Paralympic Sports (PLEEP), expressing quantitative data analyzed by descriptive statistics. Results: The results showed that, in 2014, five athletes with VI had seven sports injuries, with a prevalence of 62.5%, clinical incidence of 0.87 injuries per athlete per year, and 1.4 injuries per injured athlete. The main sports injuries were muscle strain (28.6%), groin pull (athletic pubalgia) (28.6%), and shin splints (periostitis) (28.6%). All sports injuries occurred in the lower limbs, affecting legs (71.4%) and hips (28.6%). Overload was the most frequent mechanism (57%), reported after the technical kick movement and linked to the muscle imbalance between dominant and supporting lower limbs, in addition to the postural misalignment typical of people with visual impairments. Conclusions: In summary, the Brazilian 5-a-side soccer athletes presented a pattern of overload injuries resulting from the repetition of the technical kick movement, occurring predominantly in sports competitions. Epidemiological data can contribute to the development of strategies to prevent injuries in this sport. Level of evidence II, Progressive prognostic study.